Hypoxia suppresses myofibroblast differentiation by changing RhoA activity - Leinhos, Lisa; Lévay, Magdolna (Journal of cell science, 2019)
Fibroblasts show a high range of phenotypic plasticity, including transdifferentiation into myofibroblasts. Myofibroblasts are responsible for generation of the contraction forces that are important for wound healing and scar formation. Overactive myofibroblasts, by contrast, are involved in abnormal scarring. Cell stretching and extracellular signals such as transforming growth factor β can induce the myofibroblastic program, whereas microenvironmental conditions such as reduced tissue oxygenation have an inhibitory effect. We investigated the effects of hypoxia on myofibroblastic properties and linked this to RhoA activity. Hypoxia reversed the myofibroblastic phenotype of primary fibroblasts. This was accompanied by decreased αSMA (ACTA2) expression, alterations in cell contractility, actin reorganization and RhoA activity. We identified a hypoxia-inducible induction of ARHGAP29, which is critically involved in myocardin-related transcription factor-A (MRTF-A) signaling, the differentiation state of myofibroblasts and modulates RhoA activity. This novel link between hypoxia and MRTF-A signaling is likely to be important for ischemia-induced tissue remodeling and the fibrotic response. - This article has an associated First Person interview with the first author of the paper.